Administrative reforms and performance of local public policies - Dias, Á.; Curto, H. (International Journal of Public Sector Management, 2014)
Purpose – The purpose of this paper is to clarify the relationship between administrative reform in Portugal and the impacts on the dependence of local governments in the face of budgetary resources of state and local municipal revenue collection, which is understood as a form, among others, participation civil society in local public policies. Design/methodology/approach – The study opts for an exploratory analysis using the grounded theory approach, including the use of data relating to local government structures and partnerships with the private sector, based on the main lines of the public administration reform. The data were supplemented by documentary analysis, including legislative documents and papers in specialized area of administrative decentralization and civil society participation in local public policies. Findings – The paper provides empirical insights about how the increased participation of civil society in local public policies is associated with less reliance on state budgets and a greater number of local managerial structures. Research limitations/implications – Due to the chosen research approach, the results cannot be generalized. A comparative study between several countries could bring several interesting insights. Social implications – The paper includes implications for economic and social development of new public policies in the context of administrative reforms. Originality/value – This paper makes several theoretical and empirical contributions on this research field specially about local public manager’s decisions for financial resources transfers within the active policy of sustainable local development.